Mouse Models of β-cell K(ATP) Channel Dysfunction - Brereton, Melissa F (Drug Discov Today Dis Models, 2013)
ATP-sensitive K(+) (K(ATP)) channels in pancreatic β-cells couple glucose metabolism to insulin secretion. Reduced K(ATP) channel activity produces excessive insulin release and hyperinsulinism whereas increased K(ATP) channel activity leads to lower insulin secretion and diabetes. Paradoxically, mice with genetic deletion of K(ATP) channels, or loss-of-function mutations, are only transiently hypoglycaemic during the neonatal period and often display reduced glucose-stimulated insulin secretion subsequently. Mice with K(ATP) channel gain-of-function mutations are hyperglycaemic and have impaired glucose-stimulated insulin secretion, a phenotype that accurately mimics human diabetes. This review discusses how mice expressing altered K(ATP) channels have provided valuable insight into β-cell function.